2019
DOI: 10.1093/ecco-jcc/jjz181
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of the Intersphincteric Fistula Tract and Endorectal Advancement Flap for High Perianal Fistulas in Crohn’s Disease: A Retrospective Cohort Study

Abstract: Abstract Background and Aims Ligation of the intersphincteric fistula tract [LIFT] and advancement flap [AF] procedures are well-established, sphincter-preserving procedures for closure of high perianal fistulas. As surgical fistula closure is not commonly offered in Crohn’s disease patients, long-term data are limited. This study aims to evaluate outcomes after LIFT and AF in Crohn’s high pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Studies suggest that it has comparable success rates to the more commonly used advancement flap [2]. Even in patients with Crohn's fistulas, promising results concerning clinical and radiological healing as well as low rates of incontinence have been reported [3]. The video (Video S1 in the online Supporting Information) starts with MRI images of a patient with a transsphincteric fistula for which he has had seton drainage for the last 5 months to create an epithelialized tract to prevent (recurrent) abscess formation [4].…”
Section: Supporting Informationmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies suggest that it has comparable success rates to the more commonly used advancement flap [2]. Even in patients with Crohn's fistulas, promising results concerning clinical and radiological healing as well as low rates of incontinence have been reported [3]. The video (Video S1 in the online Supporting Information) starts with MRI images of a patient with a transsphincteric fistula for which he has had seton drainage for the last 5 months to create an epithelialized tract to prevent (recurrent) abscess formation [4].…”
Section: Supporting Informationmentioning
confidence: 98%
“…In a cadaveric model, Pauli et al [2] described a novel method of open PH repair utilizing retromuscular dissection, posterior component separation via transversus abdominis release (TAR) and lateralization of the bowel utilizing a modified Sugarbaker mesh configuration within the retromuscular space. Belyansky et al [3] applied a robotic technique for PH in an effort to reduce wound morbidity and length of hospitalization, while still providing a secure and durable repair. In this educational video, we describe a robotic retromuscular PH repair with TAR, along with lateralization of the stoma conduit (the modified Sugarbaker technique).…”
Section: Supporting Informationmentioning
confidence: 99%
“…We performed a sub‐study of a previously performed retrospective cohort study conducted at the Amsterdam University Medical Centres [10]. That study included all consecutive Crohn's patients treated for high perianal fistulas with LIFT or AF between January 2007 and February 2018.…”
Section: Methodsmentioning
confidence: 99%
“…So far, there are limited data on the behaviour and structural assessment of perianal fistulas after the LIFT procedure. The clinical and radiological healing, recurrence and incontinence rates of Crohn's patients undergoing LIFT and AF were evaluated in a retrospective study [10]. This study demonstrated MRI healing in 53% of LIFT procedures; however, no standardized assessment of radiological healing was used.…”
Section: Introductionmentioning
confidence: 99%
“…Healing of the excluded fistula pathway is expected over time. In the absence of proctitis or stenosis, this is a good therapeutic option with the advantage of avoiding extensive or difficult-to-heal wounds and a success rate of approximately 50%[ 10 , 19 ] (Table 2 )[ 20 - 25 ].…”
Section: Treatment Options For Complex Fistulasmentioning
confidence: 99%